2003
DOI: 10.1177/1051228403013003007
|View full text |Cite
|
Sign up to set email alerts
|

Brain CT and MRI Findings in 100 Consecutive Patients with Intracranial Tuberculoma

Abstract: Multiple tuberculomas and infratentorial locations were more common in the authors' patient population than in previous reports. The MRI signal characteristics of intracranial tuberculoma are extremely diverse. An isointense or hypointense core with a hyperintense rim on T2-weighted and FLAIR images is the most common presentation. Core hypointensity of lesions on these images is related to necrosis and the large number of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Prognosis of tuberculoma patients was good while cerebral infarcts led to poor prognosis. Previous studies have shown presence of tuberculoma in 16%–40% patients with TB meningitis 69. Tuberculoma most likely represents an immune response to tuberculous brain parenchymal infections.…”
Section: Discussionmentioning
confidence: 95%
“…Prognosis of tuberculoma patients was good while cerebral infarcts led to poor prognosis. Previous studies have shown presence of tuberculoma in 16%–40% patients with TB meningitis 69. Tuberculoma most likely represents an immune response to tuberculous brain parenchymal infections.…”
Section: Discussionmentioning
confidence: 95%
“…The findings on this CT scan, which favour tuberculosis over NCC, are the irregularity of the shape of some of the nodular lesions, varying enhancement patterns, considerable peri-lesional oedema, and increased meningeal perivascular enhancement 3. The girl recovered fully with continued anti-tuberculous treatment and supplemental steroids.…”
mentioning
confidence: 82%
“…Based on the child's medical history it was thought that the lesion could be consistent with a calcified parenchymal granulomata that can be seen in up to 20% of patients with a history of tuberculosis 1. However, the histological evaluation revealed a heterotopic ossification most consistent with a calcified cavernous angioma.…”
Section: Descriptionmentioning
confidence: 99%